MoS2 Quantum Dot@Polyaniline Inorganic-Organic Nanohybrids for in Vivo Dual-Modal Imaging Guided Synergistic Photothermal/Radiation Therapy - Wang, Jinping; Tan, Xiaoxiao; Pang, Xiaojuan; Liu, Li; Tan, Fengping; Li, Nan (ACS applied materials & interfaces, 2016)
In this study, we introduce a versatile nanomaterial based on MoS2 quantum dot@polyaniline (MoS2@PANI) inorganic-organic nanohybrids, which exhibit good potential to not only enhance photoaccoustic (PA) imaging/X-ray computed tomography (CT) signal but also perform efficient radiotherapy (RT)/photothermal therapy (PTT) of cancer. Upon the intravenous injection of MoS2@PANI hybrid nanoparticles, the in vivo tumor could be precisely positioned and thoroughly eliminated under the PA/CT image-guided combination therapy of PTT/RT. This versatile nanohybrid could show good potential to facilitate simultaneously dual-modal imaging and synergetic PTT/RT to realize better anticancer efficiency.